Glucose induced intracellular ionic change in pancreatic islets of rat on inhibition of Na+/K+ pump by ouabain and its relation with insulin secretion - Chowdhury, AN; Saha, S; Saha, S; Ali, L (Journal of Dhaka National Medical College & Hospital, 2013)
Glucose is the primary physiological stimulator of insulin release. Na+/K+ pump has a major role in modulating the glucose action. Rat pancreatic islets were isolated by collagenase digestion. The concentration of ions in the homogenized islets were measured by Ion-sensitive Electrode based autoanalyzer. Inhibition of Na+/K+ pump by ouabain resulted in gradual increase of intracellular Na+, decrease of K+, increase of Ca++ and decrease of Mg++ compared to the physiological medium. The changes of K+ paralleled by a rise of Na+ in the media indicate that a pump-related effect seems to be more plausible for the difference in ionic changes. J.Dhaka National Med. Coll. Hos. 2013; 19 (02): 46-48